REALITAS SOSIAL DALAM NOVEL PULANG KARYA LEILA S. CHUDORI: PERSPEKTIF REALISME SOSIALIS GEORG LUKACS - Arifin, Moch. Zainul (Kantor Bahasa Banten, 2019)
Literary works as a reflection of society in their era. As a reflection of society, literary works raise the culture of society by the time or before the literary work was written. Leila S. Chudori's novel entitled Pulang can be said to be a historical work by bringing up major historical events namely the bloody tragedy of 30 September 1965, the French revolution in 1968 and also the events of 1998 in Indonesia. According to Lukacs, historical novels and social novels are the same because a social event in the past will be history for the present generation. Based on this, this study uses Georg Lukacs's theory of socialism realism. The theory states that the pure fact of nature arises when a real world phenomenon is placed (in the mind or in reality) into an environment where its laws can be monitored without the need for internal intervention. In doing so, we will be arrived at an understanding of the external forms of phenomena and think of them as forms, in which the deepest core can certainly emerge. With simple language the knowledge of the totality of facts from events must be understood the real existence and the deepest core of the facts. In Pulang's novel by Leila S. Chudori, there is a social reality that has never been learned at school. Facts such as the existence of political exiles that are adrift in Europe, torture and slaughter of victims of wrongful arrests, and so on. That explains how the history we learn today is only history made by irresponsible people. Therefore, the social reality in the novel Le Pulang S. Chudori's Pulang is a forgotten Indonesian community life.